Axiological Potential of Publicistic Text in Teaching the Russian Language (Proceedings of Southern Federal University. Philology, 2020)
The authors, based on the processes of implementation of the axiological approach in modern education, introduce the concept of axiological potential of a publicistic text into methodological circulation and justify it. This concept allows us to combine the cognitive orientation of the process of teaching the Russian language, understanding the text and its orientation to the formation of the spiritual and value sphere of the students’ personality. The article deals with the content elements and properties of publicistic text that make it possible to contain an axiological potential.Key words: axiological approach, teaching the Russian language, axiological potential, publicistic text, understanding of the text, the role of the word in the text, key words, types of text information.DOI 10.18522/1995-0640-2020-2-217-223